Making the road by walking : the evolution of the South African constitution - Bohler-Muller, Narnia; Cosser, Michael; Pienaar, Gary (2018)
"This engaging, readable law book is timely for many reasons. In this period of political turmoil, amidst allegations of bare-faced large-scale grabbing by greedy politicians and their confederates, the principles and mechanisms of our Constitution become more acutely important than ever. Over the last quarter-century or so, through our courts' judgments, delivered without fear or favour, the Constitution has begun to breathe life. Much challenge and much peril and much work still lie ahead. But some of the vibrancy and influence the Constitution has already attained may be traced to the voices and personalities of those behind the judgments: the judges who write them. This book looks at the character and thinking of some of the judges who have helped to start the process of making our Constitution real. The text reminds us that behind the structures of state and the mechanisms of power stand human beings, in all their frailty, but also in all their courage and determination to make our country better for the poorest in it. In other words, judges who take seriously the promise of constitutional governance and of social justice under law."--
Introduction / Michael Cosser, Narnia Bohler-Muller & Gary Pienaar -- The constitutionalist concept of Justice L. Ackermann : evolution by revolution / Jonathan Klaaren -- A mensch on the Bench : the place of the sacred in the secular jurisprudence of Justice Richard Goldstone / Michael Cosser -- The advocate, peacemaker, judge and activist : a chronicle on the contributions of Justice Johann Kriegler to South African jurisprudence Khulekani Moyo -- Breaking the chains of discrimination and forging new bonds : the extraordinary journey of Justice Yvonne Mokgoro / Narnia Bohler-Muller, Marie Wentsel & Johan Viljoen -- Justice O'Regan : finding the Aristotelian golden 'middle way' / Gary Pienaar -- Infusing the Constitution with 'an ethic of care' : the humane jurisprudence of Justice Albie Sachs / Narnia Bohler-Muller & Thobekile Zikhali -- The functional constitutionalism of Justice Thembile Skweyiya / Ntandokayise Ndlovu * Melissa Omino -- Transformation as constitutional imperative : Justice Zak Yacoob and the making of a civil practice / Vasu Reddy & Sarah Chiumbu.
Includes bibliographical references.
Keywords: South Africa; Constitution of the Republic of South Africa, 1996 (South Africa); Judges -- South Africa; Jurisprudence -- South Africa; Constitutional history -- South Africa; Constitutional history; Judges; Jurisprudence; South Africa -- Constitution; South Africa; Constitution